Gambaran Family Care Giver Burden dalam Merawat Anggota Keluarga dengan Skizofrenia di Wilayah Kerja Puskesmas Sutojayan Kabupaten Blitar - Nawang Wulandari (STIKes Patria Husada Blitar, 2016)
When someone is diagnosed with positive schizophrenia, there will be changes toward their life. Patients who previously have the ability to perform daily activities, in this conditions will always need help and assistance in fulfilling their life, especially the family members who are in charge in the caring. Various changes will certainly have impact on the patients themselves and for those around them, especially their family care giver. Care giver are expected to use most of their time to care and to provide social support for the sake of better conditions. This research aimed to describe the family care giver burden in the caring of their family members with schizophrenia in Puskesmaas Sutojayan Blitar. The research design used descriptive approah with purposive sampling. The total sample was 24 respondents. The data collectionused questionnaires. The results showed that 10 people (41.7%) of the Family Care giver experiencing hard burden and average burden in the care of family members with schizophrenia. People should have good understanding and concern so that there would be negative stigma in people with schizophrenia so that the burden of the care giver is not increase because of the social burden obtained. When this kind of things were done, it would reduce the risk of relapse in people with scizofrenia